Comparison of a progestin-primed ovarian stimulation protocol with a flexible GnRH antagonist protocol in patients with polycystic ovary syndrome who are participating in an IVF programme: study protocol for a randomised controlled trial. Issue 12 (2nd December 2020) - Wang, Ningling; Zhu, Qianqian; Ma, Meng; Liang, Zhou; Tao, Yu; Wang, Yun; Kuang, Yanping
Abstract : Introduction: Women with polycystic ovary syndrome (PCOS) undergoing in vitro fertilization (IVF) protocols are typically characterised by an increased number of oocytes retrieved. The oocytes are often of poor quality, leading to lower pregnancy rates, higher miscarriage rates and an increased risk of developing ovarian hyperstimulation syndrome (OHSS). Since our previous preliminary study showed that a novel progestin-primed ovarian stimulation (PPOS) protocol blocked the luteinising hormone (LH) surge during IVF and achieved a higher pregnancy rate with a lower incidence of OHSS, we designed a prospective randomised controlled trial to compare the efficacy and safety of this PPOS protocol with the flexible gonadotropin-releasing hormone (GnRH) antagonist protocol in patients with PCOS who are undergoing IVF procedures. Methods and analysis: Patients with PCOS will be randomised to one of two controlled ovarian stimulation regimens—GnRH antagonist or PPOS—using a computer-generated random number. A freeze-all strategy using embryo vitrification techniques and frozen embryo transfer will be performed in both groups. The primary outcome is the live-birth rate per transfer. Secondary outcomes include the incidence of premature LH surges, the duration and total dose of human menopausal gonadotropin stimulation, the number of oocytes retrieved, the incidence of moderate or severe OHSS, the number of embryos available for transfer, implantation rates, clinical pregnancy rates, pregnancy loss rates, ectopic pregnancy rates, pregnancy and neonatal complications, and congenital anomalies. The necessary sample size for this trial was estimated as 392 participants, with 196 participants in each group. Intention-to-treat analysis was used in processing our experimental data. Ethics and dissemination: This study was approved by the Institutional Review Board of the hospital (2016-133-T82). The trial will be conducted according to the principles of the World Medical Association's Declaration of Helsinki and in accordance with Good Clinical Practice standards. The findings of this trial will be published in a peer-reviewed journal. Trial registration number: ChiCTRIPR16009580.